2011 IEEE 13th International Conference on E-Health Networking, Applications and Services 2011
DOI: 10.1109/health.2011.6026797
|View full text |Cite
|
Sign up to set email alerts
|

mHealth for the control of TB/HIV in developing countries

Abstract: mHealth (healthcare using mobile communication technologies) is being strengthened as a new tool to tackle the global crisis in inadequate workforce and patient monitoring, especially in resource-limited settings. High numbers of people living with TB/HIV fail treatment and develop resistance because they cannot maintain a high degree of adherence to their medication regimens. This paper illustrates how a simple and inexpensive SMS-based mHealth application can be used to facilitate the TB/HIV treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The use of m-health solutions to support the primary health care system in rural areas of developing countries is a very promising trend that has been explored in several projects. In Uganda the RapidSMS system was used to manage the roll out of malaria's rapid diagnostic test 8 ; in Zambia a SMS system was employed to reduce delay in sending infant HIV testing results from a centralized laboratory to remote rural health facilities; 9 in Malawi a SMS system was designed to improve communication among health workers for family planning and reproductive health in rural areas 10 and to improve influenza surveillance; 11 in Botswana m-health is used for improving clinical education, decision making, and patient adherences; 12,13 and in India a m-health systems was used to build a health information system 14 . These studies were mostly focused on improving health processes and only a few of them analysed the impact on health indicators, such as HIV virological failure.…”
Section: Introductionmentioning
confidence: 99%
“…The use of m-health solutions to support the primary health care system in rural areas of developing countries is a very promising trend that has been explored in several projects. In Uganda the RapidSMS system was used to manage the roll out of malaria's rapid diagnostic test 8 ; in Zambia a SMS system was employed to reduce delay in sending infant HIV testing results from a centralized laboratory to remote rural health facilities; 9 in Malawi a SMS system was designed to improve communication among health workers for family planning and reproductive health in rural areas 10 and to improve influenza surveillance; 11 in Botswana m-health is used for improving clinical education, decision making, and patient adherences; 12,13 and in India a m-health systems was used to build a health information system 14 . These studies were mostly focused on improving health processes and only a few of them analysed the impact on health indicators, such as HIV virological failure.…”
Section: Introductionmentioning
confidence: 99%
“…With the emerging challenges, the development of mobile technologies has provided some insights and possibilities. Governments in developing countries have partnered with stakeholders such as academics, NGOs, and telecommunications providers on mHealth initiatives that focus on significant health-care challenges (Bakshi et al 2011). Some of those initiatives are mental health related and have provided evidence that mobilebased interventions are a feasible and cost-effective way to prevent, screen, or treat mental illness.…”
Section: Mobile-based Interventions In Mental Health Carementioning
confidence: 99%
“…There are findings that encourage this postulation; for example, in Indonesia, the Midwives with Mobiles project suggested that less skilled and remote community healthcare workers were able to deliver information to the centralized provincial hospital, via a JAVA-based mobile data delivery system (Chib, 2013). Bakshi et al (2011) contend that mHealth is advantageous for developing countries because it requires low start-up costs and mobile phone services are affordable even to the poorest areas. For example, in India, there were more than 500 million mobile phone subscribers in 2010, and the rural subscriber base amounted to approximately 190 million (Shukla & Sharma, 2016).…”
Section: Mhealth and Health Outcomesmentioning
confidence: 99%